PENGARUH STRATEGI PEMASARAN 7P TERHADAP KINERJA PERUSAHAAN PADA PT. TELKOM CABANG PALOPO - M Risal; Muhammad Aqsa (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This study aims to determine the effect of marketing mix (7P) partially on company performance at PT. Telkom Palopo Branch, as well as to analyze the effect of marketing mix (7P) simultaneously on the company's performance of PT. Telkom Palopo Branch.Based on the analysis using Smart PLS, the following analysis results are obtained: Adjust R square value of 0.179 or 179%, which means the relationship between products, prices, places, promotions, employees, processes and physical facilities affect the performance of the company PT. Telkom Palopo Branch has a strong relationship, while the Adjusted R Square value of 0.116 or 116% results of sales volume is influenced by products, prices, places, promotions, employees, processes and physical facilities. The results of the F test analysis showed that the Fcount value of 3.265 was greater than that of Ft. 2.111, so that simultaneously the seven marketing strategy variables namely product, price, place, promotion, employees, processes and physical facilities significantly influenced the company's performance.The results of the t-test analysis showed that of the seven marketing strategy variables namely product, price, place, promotion, employees, physical processes and facilities, only the price variable and physical facilities had a significant effect on company performance.